IoT-based Automatic Pesticide Sprayer Control System on Guava Trees - wibowo, budi cahyo; Setyaningsih, Noor Yulita Dwi; Setiawan, Riyan _ (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
The development of the use of agricultural technology is currently very rapid to meet the increasing basic human needs, according to water guava farmers in Penanggungan village who said that in the last year there has been an increase in water guava fruit orders by consumers. Therefore, we need a tool to help farmers in terms of cultivating water guava fruit. In this case the use of technology used in the application of automatic pesticide sprayers on water apple trees based on IoT, previously spraying was carried out by farmers manually so that with this automatic pesticide sprayer it can help farmers work in guava cultivation. This monitoring system utilizes Internet of Things technology. This study uses component input outputs, including NodeMCU ESP8266, RTC sensors, relays, LCDs. The software used for system monitoring uses Blynk software. The results of the study obtained success reaching 100% with automatic spraying successfully functioning, when the time was 16.00 WIB the pump would automatically start spraying pesticides and when the time showed 16.01 the pump would stop spraying. Notifications can be sent to the Blynk app